Political regimes and foreign investment in poor countries: Insights from most similar African cases. (September 2021) - Goldsmith, Arthur A
When foreign investors choose to invest in a poor country, do they favor democracies or autocracies? Despite extensive time-series cross-national empirical work on this question, the answer is unclear. To move the debate forward, I use a novel approach based on a most-similar case design. I observe four African countries before, during, and after democratization, and evaluate whether the change in regime type over time affected their ability to attract foreign investment—both relative to their baseline level of investment and in comparison with the investment patterns of four matching countries that did not experience democratization. I also control for the effects of natural resource scarcity and abundance. My difference-in-differences pairwise case analysis indicates the introduction of competitive political institutions is immaterial for foreign investment, whereas the consolidation of these institutions conveys a small investment advantage.